Customs Representation in Simplified Customs Procedures in Republic of Croatia - Ivaković, Čedomir; Durbek, Sanja (Promet - Traffic&Transportation, 2005)
When introduced in 2000 the use of authorized consigneeand consignor status was not particularly popular among companies,despite its apparent advantages. The number of the statususers compared to the total number of exporters and importerswas almost negligible. The aim of this paper was to find outto which extent the simplified customs procedures have beenaccepted in Croatia through an objective outline of advantagesand disadvantages that the companies - users of the simplifiedprocedures face on a daily basis.